2019
DOI: 10.1002/smll.201903572
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamically Stable Mesoporous C3N7 and C3N6 with Ordered Structure and Their Excellent Performance for Oxygen Reduction Reaction

Abstract: Carbon nitrides with a high N/C atomic ratio (>2) are expected to offer superior basicity and unique electronic properties. However, the synthesis of these nanostructures is highly challenging since many parts of the CN frameworks in the carbon nitride should be replaced with thermodynamically less stable NN frameworks as the nitrogen content increases. Thermodynamically stable C3N7 and C3N6 with an ordered mesoporous structure are synthesized at 250 and 300 °C respectively via a pyrolysis process of 5‐amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…However, the conversion of the moiety A in C 3 N 5 to the moiety B in C 3 N 4 reduces the basicity, resulting in the decrease in the amount of CO 2 adsorption. The high basicity of C 3 N 5 was both confirmed by CO 2 adsorption and by MO calculation [10,12] . These observations clearly confirmed that the differences in the catalytic activity of MCN‐11 with different nitrogen contents are linked with the nature of the functional groups in the structure of these catalysts.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…However, the conversion of the moiety A in C 3 N 5 to the moiety B in C 3 N 4 reduces the basicity, resulting in the decrease in the amount of CO 2 adsorption. The high basicity of C 3 N 5 was both confirmed by CO 2 adsorption and by MO calculation [10,12] . These observations clearly confirmed that the differences in the catalytic activity of MCN‐11 with different nitrogen contents are linked with the nature of the functional groups in the structure of these catalysts.…”
Section: Resultssupporting
confidence: 64%
“…We have previously reported that the structures of carbon nitrides from 5‐amino‐1 H ‐tetrazole using KIT‐6 as hard template can be altered by varying the carbonization temperatures [5b,10a,12] . Particularly, the nitrogen contents of these materials are significantly changed as the carbonization temperature is increased.…”
Section: Resultsmentioning
confidence: 99%
“…The field is still expanding toward materials with a higher C/N ratio, such as C 3 N 7 , finding application in electrochemical oxygen reduction. [58] Heteroatom doping is a reliable method to introduce different elements into the CN backbone, effectively changing electrical, optical and morphological properties of the material. Heating trithiocyanuric acid at 650°C was reported to yield sulfur doped CN.…”
Section: Overview Of Photocatalytically Active Materialsmentioning
confidence: 99%
“…Absorption peaks at 398.5, 399.6 and 401.2 eV are responsible for excitations to π* pyridinic N , π* N=CÀ N and π* tertiary N , respectively. [27,30,33,34] A characteristic peak at 397.1 eV of the Ndoped MoS 2 is not observed in the N K-edge NEXAFS spectra of all present samples, which excludes the possibility of N-doping into the MoS 2 . [35] While the CN/MoS 2 -500 shows a dominant feature of pyridinic N, characteristics of N=CÀ N and tertiary N bonds become distinct for the CN/MoS 2 -800.…”
mentioning
confidence: 50%
“…Although Bragg reflections of CN with MoS 2 are not reflected on the XRD patterns, carbon nitride content was quantified by CHNS elemental analysis as shown in Table S1. Considering that CN experiences significant and continuous weight loss with a temperature increase, [30,31] it is believed that the decrease in the CN content is ascribed to the evaporation of partial carbon and nitrogen at elevated temperatures.…”
mentioning
confidence: 99%